26.2k views
1 vote
Whats the solution for
6g - 2h = -10
11 = h - 5g

1 Answer

7 votes

Answer: {g,h}={−3,−4}

Explanation:

System of Linear Equations entered :

[1] 6g-2h=-10

[2] 11=h-5g

Equations Simplified or Rearranged

[1] 6g - 2h = -10

[2] 5g - h = -11

// Solve equation [2] for the variable h

[2] h = 5g + 11

// Plug this in for variable h in equation [1]

[1] 6g - 2•(5g+11) = -10

[1] -4g = 12

// Solve equation [1] for the variable g

[1] 4g = - 12

[1] g = - 3

// By now we know this much :

g = -3

h = 5g+11

// Use the g value to solve for h

h = 5(-3)+11 = -4

and your solution is

{g,h} = {-3,-4}

User Jerryf
by
5.0k points